The Surfacing of Great Power Rivalries in The Indian Ocean: Indonesia’s Urgency to Empower The Indian Ocean Rim Association - Bama Andika Putra (Journal of Society and Governance, 2017)
The Indian Ocean is the third largest of the world’s oceanic divisions. As a critical sea trade route marked with the presence of strategic chokepoints such as the Strait of Hormuz, Strait of Malacca, and the Mandeb Strait, Its ever strategic position has eventually led to a potential turbulent security environment, as states fall deeper into a sense of vulnerability because of the fragile security of the region. Connecting the continents of Asia, Africa, and the Middle East, and consisting of tens of littoral states, contemporarily the Indian Ocean has been home to coercively interpreted policies which among them include China’s “String of Pearls,’ and the numerous naval exercises conducted such as the MALABAR and AUSINDEX, acting as an offensive military posturing to many. As the Indian Ocean slowly evolves being a centre stage of geopolitical supremacy contestation, the paper argues for the urgent need for the Indian Ocean Rim Association (IORA) to adopt measures in advance of the tempestuous security environment. Being the Chairman of IORA for 2015-2017, Jokowi’s ‘Global Maritime Axis’ will be tested by how he plans to respond towards the growing volatile security situation. It further argues of possible engagements Jokowi can take in order to solidify the very concept of ‘Global Maritime Axis’ that he conceived, by arguing the need for him to establish foundations of cooperation that would bind IORA member states as well as great powers which are critical towards the Indian Ocean’s sea-lanes of communication, and the need to take the step of replacing the highest authority of the IORA, to a Heads of State Summit, in order to clout more of a significant political influence in the region.Keywords: Indonesia, Indian Ocean, Regionalism, Institutionalism, Foreign Policy